Inconsistencies in Constitution Rights; Iraqi Constitution as a Case Study - Kakai, Luqman Rashid (International Journal of Humanities and Education Development (IJHED), 2023)
This study addresses a lack of compatibility or similarity between two or more facts. Discrepancies in the meta-law, body of law or law above law. The study is to find out the obstacles and challenges of rights in constitution and Iraqi constitution as a case study. In post-2003, after the fall of Saddam Hussein, new constitution been imposed on Iraq (as some scholars affirm that) by the US. Moreover, both liberalism and Islamism been pushed as a law in “Iraqi New Constitution”. The study will focus on the individual, minority, and gender rights Islamism principle in Iraqi constitution and the inconsistency between both liberalism and Islamism in Iraqi Constitution. To test our argument, the study is using quantitative data. The study finds out that Iraqi constitution articles are inconsistent with each other. What is more, there are declining in the rights of individual, minority, and women.